ANALISA FAKTOR-FAKTOR PENYEBAB KECELAKAAN PADA DAERAH RAWAN KECELAKAAN PADA RUAS JALAN SUMBA BARAT-SUMBA BARAT DAYA - Marselus Putra Mawo Kasa Sairo; I Wayan Muliawan; Putu Aryastana (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2018)
Road between Southwest Sumba-Sumba Southwestern is a country road the connects the two districts. Based on the results of the research (Alfian Dawa, 2013) in Sumba Barat-Sumba Barat Daya road segment there are 16 road segments identified as accident-prone areas. From the results of the analysis of the most vulnerable areas of accidents occur is in the segment 1 or at kilometer 4-5 as the cause has a cusum value is the highest cusum value of all cusum values at each stationation or kilometer. Thus, the authors conducted a follow-up study to further analyze 16 accident-prone areas in West Sumba-Southwest Sumba district to find out what factors caused accidents in accident-prone areas on the West Sumba-Southwest Sumba road. Having known the factors causing the occurrence of new traffic accidents can provide a solution to the number of accidents can be minimized. From the analysis of factors causing traffic accidents in 16 accident-prone areas on the West Sumba-West Sumba road segment are human factors, vehicle factors, and road and environmental factors. The most common cause of traffic accidents in 16 crash-prone areas on the West Sumba-Southwest Sumba road segment from 2011 to 2015 covering road users/human factors of 326 occurrences, in the last 5 years. While the factors of the vehicle as much as 385 incidents, as well as road and environmental factors also triggered traffic accidents because there are road marks/signs, and street lighting on 16 areas prone to accidents on West Sumba-West Sumba road.